7 plus 7x--2x plus 3 is: 7 + 7x + 2x + 3 = 0 9x + 10 = 0 9x = -10 x = -10/9 = -1 1/9
2x - 4x + 3 = 0 -2x + 3 = 0 2x = 3 x = 3/2 = 1.5
(2x+3)(2x+4)
y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.
x + 3 + 2x = x + 9 x + 2x + 3 = x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 2x + 3 = 9 2x + 3 - 3 = 9 - 3 2x + 3 - 3 = 9 - 3 2x = 9 -3 2x = 6 2x/2 = 6/2 2x/2 = 6/2 x = 6/2 x = 3
x=(y-3)/2
I presume you mean given y find x: Make x the subject: y = 2x + 3 => 2x + 3 = y => 2x = y - 3 => x = (y - 3)/2 which can also be expressed as: x = 0.5 y - 1.5
The inverse is the opposite. If you're using 'x' it will change to division.
the inverse of x+3
4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4
The inverse for f(x) = 4x + 8 isg(x) = x/4 - 2
4x plus 3 plus 2x is equivalent to expression 6x plus 3.
(2x + 3)(x + 1 ) = 2x^2 +5x +3
2x + 4x + 3 = 6x + 3
2x + 3 + 23x = 25x +3
Simplist form of 2x plus 3-10 is 2x-7.
It can be simplified to: 2x+33